Usina fotovoltaica flutuante para operação coordenada com uma usina hidrelétrica (UHE) no Paraná - Tonon, Bruno Henrique (2022)
In recent years, Brazil has faced serious problems with water scarcity, due to climate change and the increase in energy demand. Since hydroelectric plants are responsible for more than half of the electricity generated in the country, dominating the Brazilian energy matrix. Linked to this, this is the need to search for alternative energy sources and one of the most viable options today is photovoltaic energy, which is clean and sustainable energy, in addition to having little environmental impact, its cost is low compared to others energy sources, such as thermoelectric and thermonuclear. On the other hand, the reservoirs of hydroelectric plants have a large area available, which can make it feasible to install a floating photovoltaic plant to work in coordinated operation with the hydroelectric plant, and thus, in periods of water scarcity, the photovoltaic system can supply the energy demand using of the same transmission network. Therefore, this course conclusion work sought to dimension, through the use of database and specific software, a proposal for a floating photovoltaic plant with coordinated operation in the reservoir area of the second largest hydroelectric plant in the state of Paraná. To achieve the general objective of this work, QGIS, Google Earth and PVsyst software were used for dimensioning. With the results obtained from the available area, the sizing of the system was carried out in three possible scenarios of installation area of the floating photovoltaic plant. After running the simulation in the PVsyst software, the system powers, energy produced, irradiation, performance ratio, avoided CO 2 emissions, among others, were obtained. In the results, it is highlighted that the installed power in the first stage was 239.7 MWp and the avoided emissions were 926,027.6 tons of CO 2 , in the third stage, these values reached 2,397.0 MWp of installed power and 8,756,550.8 tons of CO 2 avoided. The environmental benefits and coordinated operation of the floating photovoltaic plant were presented.